Strengthening agricultural sustainability in the Ganges Delta polders: a stakeholder-centric approach to hydrological modeling - Jampani, Mahesh; Mizan, Syed Adil; Sena, Dipaka Ranjan; Matheswaran, Karthikeyan (International Water Management Institute, 2024)
A collaborative workshop brought together water management experts to tackle water and agricultural challenges in the Ganges Delta polders. These low-lying, protected areas are vital for agriculture but face threats from salinity intrusion and waterlogging. The workshop, organized by the International Water Management Institute (IWMI), International Rice Research Institute (IRRI), and Institute for Water Modelling (IWM) Bangladesh, focused on using local-scale hydrological modeling to forecast salinity and inform agricultural decisions.